Memikirkan Ulang Tentang Denominasi: Perspektif Sejarah - Purwanto, Henky (Sekolah Tinggi Teologi Kanaan Nusantara, 2022)
Questions about denominations always come up from time to time. Believers get confused and question why there are so many denominations, doesn't the Bible teach about the unity of believers, in this case of course including the church. This has made many people reject the emergence of denominations for various reasons such as assuming that denominations are products of the devil because the emergence of denominations often begins with a conflict that is contrary to God's will, namely unity. How many church leaders with different doctrines and interpretations, ideals and also powers finally decided to separate themselves and create a new denomination. Based on these things, this paper is trying to answer this question from a historical point of view of the creation of denominations and then make it the basis for the church or believers to address the various existing denominations. The research method used in this research is descriptive qualitative with historical literature research regarding the origins of denominations and their development, studying the causes of the emergence of various denominations, concluding and then drawing lessons from history that can be used to add insight to church leaders and God's congregation in responding various existing denominations as well as when facing the emergence of new denominations. From research on historical literature, it can be concluded that the solution to the emergence of various kinds of denominations that have sprung up is unity or unity which is carried out through a council which stipulates